RELATIONSHIP OF KNOWLEDGE AND ATTITUDES WITH PERSONAL HYGIENE DURING MENSTRUATION IN TEENAGERS OF SMP NEGERI 8 TETAP DISTRICT OF KAUR REGENCY - ruri maiseptya sari (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2020)
The behavior of maintaining the cleanliness of the reproductive organs, especially during menstruation, is part of health behavior. The purpose of this study was to determine the relationship between knowledge and attitudes with personal hygiene during menstruation in adolescents in SMP Negeri 8, Fixed District, Kaur Regency. This research uses a quantitative approach with the type of research analytical survey and cross sectional research design. The research population consisted of all 8 grade girls of SMP Negeri 8 Kecamatan Tetap Kaur Regency who have experienced menstruation, consisting of 3 classrooms totaling 63 students. The research sample was taken by total sampling technique totaling 63 students. The data used are primary and secondary data processed univariate and bivariate with Chi-Square statistical test. Based on the research, there were 44.4% who had good personal hygiene during menstruation and 55.6% had good personal hygiene during menstruation. There were 39.7% who had poor knowledge, 33.3% who had sufficient knowledge and 27.0% who had good knowledge. There are 38.1% who have unsupportive attitudes and 61.9% who have supportive attitudes. There is a significant relationship between knowledge and attitudes with personal hygiene during menstruation in adolescents at SMP Negeri 8 Kecamatan Tetap Kabupaten Kaur with the category of moderate relationship. Schools should provide education on reproductive health issues, especially maintaining the cleanliness of reproductive organs early to avoid reproductive diseases and the need for schools to establish school health units (UKS) so that students are more active in paying attention to their health. It is hoped that schools should provide education through the distribution of leaflets to students regarding reproductive health, especially maintaining the cleanliness of reproductive organs early to avoid reproductive diseases and the need for schools to organize school health units (UKS) so that students are more active in paying attention to their health. Keywords: Knowledge, Attitudes and Personal Hygiene During Menstruation